Bilateral Sensorimotor Impairments in Individuals with Unilateral Chronic Ankle Instability: A Systematic Review and Meta-Analysis - Xiaomei Hu; Tianyi Feng; Pan Li; Jingjing Liao; Lin Wang (Sports Medicine - Open, 2024)
Abstract Background Chronic ankle instability (CAI) is manifested by sensorimotor impairments in the sprained ankle, including deficits in sensation, motor function, and central integration or processing. These impairments have a significant impact on physical activities and daily life. Recently, some studies have suggested that bilateral deficits were observed in unilateral CAI, but contradictory evidence disputes this finding. Therefore, the objective of this study was to investigate whether bilateral sensorimotor deficits presented in individuals with unilateral CAI. Methods Without language restriction, the following databases were retrieved from database inception up until 3 November 2023, including PubMed, WOS, EMBASE, Cochrane, SPORTDiscus and CINAHL. Case-control and cross-sectional studies that investigated bilateral sensorimotor functions in individuals with unilateral CAI were included. Sensorimotor functions contained static and dynamic balance, functional performance, muscle strength and activation, as well as sensation. Outcome measures contained centre-of-pressure parameters, normalised reach distance, activation time and magnitude of muscle, sensory errors and threshold. The risk of bias and quality assessment of included studies were evaluated using a standardised tool recommended by the Cochrane Collaboration and the Epidemiological Appraisal Instrument, respectively. To explore the potential bilateral deficits associated with unilateral CAI, a comprehensive meta-analysis was conducted using Review Manager version 5.4. The analysis compared the injured limb of unilateral CAI with healthy controls and the uninjured limb with healthy controls. The main focus of this study was to investigate the differences between the uninjured limb and healthy controls. A random-effects model was employed and effect sizes were estimated using the standardised mean difference (SMD) with 95% confidence intervals (CIs). Effect sizes were deemed as weak (0.2–0.5), moderate (0.5–0.8), or large (> 0.8). Results A total of 11,442 studies were found; 30 studies were contained in the systematic review and 20 studies were included in the meta-analysis. Compared with healthy controls, those with unilateral CAI presented weak to moderate impairments in their uninjured limbs in static balance with eyes open (SMD = 0.32, 95% CI: 0.08 to 0.56), functional performance (SMD = 0.37; 95% CI: 0.08 to 0.67), kinesthesia (SMD = 0.52; 95% CI: 0.09 to 0.95) and tibialis anterior activation (SMD = 0.60, 95% CI: 0.19 to 1.01). There were no significant differences in other comparisons between the uninjured limb and healthy controls. Conclusions Patients with unilateral CAI may present bilateral deficits in static balance with eyes open, functional performance and kinaesthesia. However, further evidence is required to confirm this point due to limited studies included in some analyses and small effect size. Registration The protocol was registered in the International Prospective Register of Systematic Reviews platform (CRD: 42,022,375,855).